2010
DOI: 10.1051/0004-6361/201014371
|View full text |Cite
|
Sign up to set email alerts
|

X-ray and multiwavelength view of NGC 4278

Abstract: Context. The emission mechanism responsible for the bulk of energy from radio to X-rays in low ionization emission line regions (LINERs) and low luminosity active galactic nuclei (LLAGN) has been long debated. Based on UV to X-ray and radio to UV flux ratios, some argue that LINERs/LLAGN are a scaled-down version of their more luminous predecessors Seyfert galaxies. Others, based on the lack of X-ray short (hours) time-scale variability, the non detection of an iron line at 6.4 keV, and the faint UV emission c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 74 publications
(100 reference statements)
5
32
0
Order By: Relevance
“…Despite this, the same spectral variation was found (Norm 2 ). Younes et al (2010) found for NGC 4278 a 31% (20%) variation at soft (hard) energies, where we found 26% (29%) variation for the same observations. Pian et al (2010) found long-term variability in two of their four type 1 LINERs using Swift data.…”
Section: Short and Long Timescale Variabilitysupporting
confidence: 87%
See 2 more Smart Citations
“…Despite this, the same spectral variation was found (Norm 2 ). Younes et al (2010) found for NGC 4278 a 31% (20%) variation at soft (hard) energies, where we found 26% (29%) variation for the same observations. Pian et al (2010) found long-term variability in two of their four type 1 LINERs using Swift data.…”
Section: Short and Long Timescale Variabilitysupporting
confidence: 87%
“…The nuclear variability of this source has been previously studied by Younes et al (2010). They concluded that long timescale (months) variability is detected with a flux increase of a factor of ∼3 on a timescale of a few months and a factor of 5 between the faintest and the brightest observation separated by about three years.…”
Section: Appendix A: Notes and Comparisons With Previous Results For mentioning
confidence: 90%
See 1 more Smart Citation
“…While the different Chandra observations did not show short-term variability, during the XMM-Newton observation Younes et al (2010) found a flux increase of a 10% in few hours. With the same dataset, HG13 obtained a 3% variation in the same time range, the difference being most probably due to the different apertures used for the analysis (10 vs. 25 ).…”
Section: B11 Ngc 4278mentioning
confidence: 79%
“…Pellegrini et al (2012) studied Chandra observations of NGC 4278 and found an X-ray luminosity decrease by a factor of ∼18 between 2005 and 2010. Younes et al (2010) detected a factor of ∼3 flux increase on a timescale of a few months and a variation of a factor of 5 between the faintest and brightest observations (separated by about three years). We used three of these observations (others were affected by pileup or did not meet the minimum count number), and found that our spectral fittings agreed well with theirs, although we found weaker variations in luminosities.…”
Section: B11 Ngc 4278mentioning
confidence: 90%